An Interrupted Pummerer/Nickel‐Catalysed Cross‐Coupling Sequence. Issue 31 (5th July 2018) - Aukland, Miles H.; Talbot, Fabien J. T.; Fernández‐Salas, José A.; Ball, Matthew; Pulis, Alexander P.; Procter, David J.
Abstract: An interrupted Pummerer/nickel‐catalysed cross‐coupling strategy has been developed and used in the elaboration of styrenes. The operationally simple method can be carried out as a one‐pot process, involves the direct formation of stable alkenyl sulfonium salt intermediates, utilises a commercially available sulfoxide, catalyst, and ligand, operates at ambient temperature, accommodates sp‐, sp 2 ‐, and sp 3 ‐hybridised organozinc coupling partners, and delivers functionalised styrene products in high yields over two steps. An interrupted Pummerer/cyclisation approach has also been used to access carbo‐ and heterocyclic alkenyl sulfonium salts for cross‐coupling. Abstract : Feel free to interrupt : Styrenes were activated under metal‐free conditions by an interrupted Pummerer process. The resulting stable alkenyl sulfonium salts underwent nickel‐catalysed cross‐coupling under simple, mild conditions. The versatile sequence could be carried out as a one‐pot process with a range of organozinc partners to form di‐, tri‐, and tetrasubstituted alkene products.